Life-World' in Hans-Georg Gadamer's Hermeneutic Philosophy - Monteagudo Valdez, Cecilia (Pontificia Universidad Católica del Perú - Departamento de Humanidades, 2013)
This paper examines the presence of the Husserlian operative concept of the lifeworldin Hans-Georg Gadamer's hermeneutic philosophy. It is suggested that, regardless of Gadamer·s criticisms to the method and the foundational project of phenomenology, it is possible to highlight in his interpretation of Husserl's work relevant shared aspects for the clarification of his own position. These are concerned with the struggle against objectivism and its alienating effects against cultural and social praxis, as well as the rehabilitation of a pre-reflective space previous to logic and scientific research, which are regarded by both authors as the ground where all cultural products are rooted.